Review on Emission of Radiated Electromagnetic Fields from Train Pantograph Arcing - Rashid, Md Mamun Ur; Tuli, Tadele Belay (Engineering International, 2018)
Pantograph arc is one of the most common and yet unavoidable difficulties in electrified railways. During winter the intensity of arcing increases due to ice layer on the overhead catenary wire. In AC traction system, the sinusoidal waveforms of the supply voltage and current distort due to pantograph arcing. It generates both conducted and radiated emission in a wide band. Both the DC component and higher order conducted and radiated emission increases with line speed. The amplitude of the DC voltage shows a wide variation concerning train speed, applied voltage, type of electrical load, the gap between the contact wire and the pantograph and current. In this paper, pantograph arcing and its effects on the railway vehicles are described. Sliding contact between the pantograph contact strips and the catenary contact wire is illustrated with the emphasis on the pantograph arcing. Arc characteristics, formation methods, extinction and resignation of the arc are studied. This paper presents a comprehensive review on pantograph arcing and its effects near radio-based mobile communications and other signaling instruments and some other related areas.